Aplicação de cavacos de titânio para produção de revestimentos resistentes ao desgaste - Fagundes Júnior, José Gedael [UNESP] (2014)
Equipments of the sugar-cane plants and mineral extraction are submitted to severe abrasive wear conditions. Welded hardfacing are usually applied to repair that kind of damage where commercial chromium/carbon-rich welding consumables have usually been employed. In the present work was investigated the microstructure of experimental hardfacings made by addition of residues (chips) collected from machining of ASTM F67 (unalloyed Ti, grade 4) alloy. Mixtures with different carbide-formers (Cr/Nb ferro-alloys) were also tested. Two layers of pure chips (Ti), chips plus Fe-Cr (Ti-Cr), and chips plus Fe-Nb (Ti-Nb) were applied on low-carbon steel specimens by GTAW/TIG process. The microstructure of hardfacing layers was observed by optical and scanning electron microscopy (SEM) equipped with EDS microanalysis. The microstructural characterization has determined that carbide distributions change significantly with the chemical nature of the hardfacing. SEM observations coupled with EDS microanalysis have confirmed the formation of complex carbides within metal weld, whose stoichiometry was determined by X-rays diffraction (XRD) analysis. Mixed carbides MC-type and some cementite have been found. As a result it was suggested that using of ASTM F67 chips as carbide formers for composition of welding consumables can contribute to improve wear resistance of hardfacings, if compared with traditional chromium-based hardfacings.